Clinical Hematology International - Mohty, Mohamad; Nagler, Arnon; Savani, Bipin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Clinical Hematology International is the official journal of the International Academy for Clinical Hematology (IACH) which aims to promote the highest quality practices in the field of clinical hematology. The journal is an open-access, international, peer-reviewed, electronic publication which is openly distributed worldwide. Clinical Hematology International publishes articles in the broad field of clinical hematology, reporting on novel and important findings in clinical and translational research. The broad scope of the journal covers topics such as benign and malignant hematology, hematopoietic cell transplantation and cellular therapy. The journal publishes a range of article types including original studies, reviews, perspectives, editorials and correspondences to the Editor that elaborate on significant advances in clinical practice in hematology .
Keywords: Medicine; Clinical Medicine